A Critical Review of Hardin’s Tragedy of the Commons Model (1968): A Case Study of the Segara Anakan Community, Cilacap, Central Java - Prihandoko Sanjatmiko (Antropologi Indonesia, 2018)
This paper aims to contribute to the theory of common property that has been developed since the 1960s by explaining the dynamics involved in the management of resources that are in transition, from being held “in common” (common pool resources) to being privately owned (as private property) or vice versa, through compromises made among the actors in the communal legitimacy. Qualitative research was conducted in Ujung Alang and Klaces village, Kampung Laut sub district, the Cilacap regency, Central Java, Indonesia. The findings of this study indicate that landscape changes can cause changes in the agrarian structure in the form of changes in resource ownership as the resources convert from common property to private property. At the same time, some other resources are transformed from private property to common property. Both processes are possible due to the roles of actors who are capable of using their power relations. Hardin’s previously established Tragedy of the Commons model can be expanded into a dynamic theory through the incorporation of the theory of the actors’ access to power relations.